RANCANG BANGUN SISTEM INTENET OF THINGS DALAM PENGECEKAN KERUSAKAN BARANG BERBASIS BERBASIS ANDROID - Novian, Mikhael Dio; Asshiddiq, Fajar Rasyid; Abdullah, Fadil; Anggara, Ikbal; Noval, Muhammad; zulfadillah, zulfadillah; Fathani, Moh. Ayip (Politeknik META Industri Cikarang, 2025)
Product damage is a common problem in storage and distribution processes, particularly due to impacts, temperature fluctuations, and uncontrolled humidity. Limitations of manual inspection systems often result in inefficient and non–real-time damage detection. This study aims to design and develop an Internet of Things (IoT) system based on Android for automated and integrated product damage inspection. The proposed system utilizes sensors to detect physical parameters that may indicate potential damage, such as vibration and environmental conditions. Sensor data are transmitted wirelessly to a server and presented through an Android application, enabling real-time monitoring of product conditions. The research methodology includes hardware design, software development, and functional system testing. The experimental results demonstrate that the system is capable of detecting and displaying indications of product damage with good reliability and fast response time. Therefore, the developed system is expected to improve monitoring efficiency, reduce the risk of product damage, and support more accurate decision-making.